Desempenho de sementes de feijão tratadas com biotivador - Carvalho, Lara Sulamita Modesto Jacó de (2012)
The bean (Phaseolus vulgaris L.) is grown in all regionsof Brazil andis characterized asanimportant sourceof protein in food, especially forlow-income population, also serving as a source of iron, and carbohydrates. Bioactivators are complex organic substances that can alter the plant growth. Among bioactivators, the commercial producer HX® activates several physiological responses such as the expression of proteins. The objective of this study was to evaluate the physiological quality of common bean seeds treated with a bioactivator. Seeds of bean cultivar Perola. The seeds were first disinfected and then be treated with an equivalent dose of 5 ml per kg seeds were sown in plastic pots with a capacity of 280 mL. And gauged by the following tests: germination, height, and weight ofthe plant.Based on these resultswe conclude that: the biativador HX® promotes increase in the height of bean plants to seven days after sowing, the dry matter of root, shoot and to tal be an plants is greatest between 14 and 28 days after sowing when the seeds are treated with bioactivator HX®.